Seeing infants with new eyes [videorecording] - Beatty, Tinker; Gerber, Magda (National Association for the Education of Young Children, 1984)
Examines the child rearing philosophies of Magda Gerber and her Hungarian teacher, Dr. Emmi Pikler. Stresses that infants should be treated and respected as individuals.